The influence of financial socialization, financial behavior, locus of control and financial stress on young adults' financial vulnerability - Anthony, Mervin; Sabri, Mohamad Fazli; Wijekoon, Rusitha; Abdul Rahim, Husniyah; Abdullah, Haslinda; Othman, Mohd. Amim; Md. Yusoff, Irwan Syah (Human Resource Management Academic Research Society, 2021)
The degree of Malaysian household debt remains high, at present among the highest in Asia, raising concerns about its sustainability. Based on that existing issue and results of the several studies the question is arisen regarding what needs to be done to address the high levels of financial vulnerability experienced by the Malaysians, especially the young adults. Therefore, major objective of the current study was to examine the major determinants that affect financial vulnerability, and allow policymakers to address the above issue. A multi stage random sampling method was performed to draw a representative sample of Malaysian young adults, and 651 duly filled responses were received through the self-administered questionnaire. As stated by the multiple regression results, 53.1% of the total variance of financial vulnerability was explained by the model. Determinants of financial vulnerability examined by this study comprise financial socialization, financial behavior, locus of control, and financial stress; all of them were significantly related with the financial vulnerability and except financial stress, all other three determinants were shown negative relationships. Therefore, current study has both the theoretical and practical contributions, and offers experts with actionable insights regarding the determinants of young adults’ financial vulnerability when designing policies to prevent them from moving from a state of lower to higher financial vulnerability overtime.